More than a metaphor: How the understanding of power is grounded in experience - Schubert, T.; Waldzus, S.; Seibt, B. (Spatial dimensions of social thought, 2011)
Judgment and thinking about power, a universal form of human sociality, is intimately tied to spatial cues: Nonverbal communication, cultural produc-tion of power symbols, and metaphors of power all make use of the vertical spatial dimension. We argue that this overlap is due to a grounding of the concept of power in spatial thought. Evidence confirming this proposition can be found in experiments showing the impact of highly schematized spatial cues on judgments of power. We will discuss how semantic network theories, embodied theories of cognition, and conceptual metaphor theory fare in explaining and predicting the combined evidence on nonverbal be-havior, cultural production, and metaphors. In particular, we will ask what role language in the form of metaphors plays for our understanding of pow-er as size and elevation: Whether it is causal, or mainly an outcome of other processes that are not based on language.